Pengaruh Kualitas Pelayanan Jasa Driver GrabFood Terhadap Kepuasan Pelanggan (Studi Di Kabupaten Banyumas) - Afrianingsih, Fera; Farisi, Herdian; Safitri, Anjar (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Technology and information use results in new habit in all aspects of life. The changing lifestyle in community today indicates a shift to modern one by utilizing technology. This requires business actors to change how they run their business to get advantage and to be competitive in marketplace. PT Grab Technology Indonesia is one of corporations following technology development today. One of its features, GrabFood, facilitates food order as it can be done anytime and anywhere through mobile service provided. This research aims to analyze the effect of service quality dimension provided by GrabFood driver on customer satisfaction in Banyumas Regency. The variable tested includes five dimensions of SERVQUAL: tangible, reliability, responsiveness, assurance, and empathy. Data were collected through distributing questionnaire to 100 respondents constituting the users of GrabFood service in Banyumas Regency. Data analysis was carried out using validity, reliability and multiple linear regression tests. The result of research shows that reliability, responsiveness, and assurance have significant effect on customer satisfaction, while tangible and empathy do not have significant effect. Simultaneously, service quality evidently affects customer satisfaction